KELEMBAGAAN KEMITRAAN HULU HILIR UNTUK PASOKAN AIR DAS CIDANAU, PROVINSI BANTEN - Nur Laila; Kukuh Murtilaksono; Bramasto Nugroho (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2014)
Upstream and downstream institutional partnerships in Cidanau watershed had been built in 2005 using payment for environmental services (PES) approach. Among stakeholders, partners involved in the mechanism are Krakatau Tirta Industri (KTI) Company as a water beneficiary for commercial use and up-stream farmer groups as a service provider, and facilitated by a multistakeholder watershed forum namely Forum Komunikasi DAS Cidanau (FKDC). The farmers were paid for their role in conserving land and maintaining of tree stand in accordance with number of trees and contract period which is agreed by both parties. The study aimsto formulate partnership institution which is intended by both parties for the sustainability of Cidanau water supply. This is a qualitative research with a case study approach. Data analysis in general was referred to Institutional Analysis Development (IAD) which was developed by Ostrom (2008). This research applied purposive sampling and snowball sampling. The result of the research shows that majority of land ownership of the involved farmers is private property which is cultivated to meet their daily need. In the first period of contract (2005-2009) there were 4 farmer groups involved but 2 groups ceased to be the members of PES; and in the second period (2010-2014) there were 5 PES groups signed the contract including extended groups. Improvement is necessary in order to achieve optimum benefit of Cidanau water supply and involving parties. Apart from the mechanism rule, institutionalization of FKDC needs to be improved and strengthened in manifesting partnership institution of Cidanau water supply. The necessary approach to prevent contract discontinuation in other village as has been experienced in Cibojong and Kadu Agung villages area) invidual approach for heterogenous types of farmer communities, b) establishment of village alternative financial institutions, c) possibiliy of thinning certain diameter oftrees, d) assessment of the incentive to farmer groups as environmental service providers.